Health-related quality of life in patients with non-communicable disease: study protocol of a cross-sectional survey - Els Clays; Pauline Boeckxstaens; Delphine De Smedt; Peter Pype; Brecht Devleesschauwer; Lisa Van Wilder; Diego Schrans (BMJ Open)
Introduction Non-communicable diseases (NCDs) are associated with lower health-related quality of life (HRQoL). However, knowledge about those diseases and predictors with a greater impact on patients’ HRQoL as well as knowledge on the complex relationship between HRQoL and comorbidities is lacking. The aim of this study is to assess the impact of NCDs on patients’ HRQoL, with a focus on multimorbidity and socioeconomic status.Methods and analysis A primary care-based cross-sectional study is conducted in Flanders (Belgium). Study participants (≥18 years) are medically diagnosed with at least one of the following diseases: cardiometabolic disorders, mental disorders and musculoskeletal disorders. A minimum of 50 general practitioners will participate to recruit participants (convenient sample) and a total of 531 patients will be enrolled (voluntary response sample). Each participant will complete a paper-based questionnaire to gather research outcomes. Statistical analyses will be performed using multiple linear regression models with HRQoL as main outcome parameter, adjusted for possible confounders. This study will generate new evidence on the key predictors of HRQoL in patients with NCDs, and particularly provide new insights in multimorbidity to improve the quality of care in primary care, to support patients’ self-management and to allocate resources more effectively.Ethics and dissemination The study has been approved by the Ethical Committee of Ghent University Hospital, Ghent, Belgium (reference number: B670201939629) prior to the beginning of the recruitment. Study results will be disseminated through peer-reviewed publications and conference presentations.